Sammlung Metzger : Zeitgenössische Malerei aus der Bundesrepublik Deutschland. - Felix, Zdenek (Budapest : Mücsarnok Kunsthalle, 1984)
Adamski, Hans Peter ; Anzinger, Siegfried ; Barfuss, Ina ; Bauch, Michael ; Bömmels, Peter ; Büttner, Werner ; Dahn, Walter ; Dokoupil, Georg Jiri ; Fetting, Rainer ; Kever, Gerard ; Kippenberger, Martin ; Middendorf, Helmut ; Naschberger, Gerhard ; Oehlen, Albert ; Oehlen, Markus ; Schuze, Andreas ; Wawrin, Isolde ; Zimmer, Bernd
Sammlung Metzger : Zeitgenössische Malerei aus der Bundesrepublik Deutschland, Mücsarnok Kunsthalle, Budapest, 24. Januar - 26. Februar 1984
boek
Keywords: Duitsland